Rancang Bangun Online Analytical Processing (Olap) Untuk Penyajian Data Akademik Stikom Surabaya - Wijaya, Eric; Wurijanto, Tutut; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Abstract: STIKOM Surabaya is a university that focus in computer science. Now, STIKOM Surabaya has ransaction data more than 10 years that saved in its database. That data never been used optimally cause data never been transferred to data warehouse. With all of this data, it makes STIKOM Surabaya rich of data but poor with information so that every decision cannot be taken well and quickly. Reports that management required always be populated from transactional data and it takes long time because relationship in transactional data is not suitable with reporting. Each time new report requested by management, it will also takes longer time because user must track each table to make that report. Data warehouse is a solution that can make reports faster and more accurate. Transactional data will be transferred to data warehouse and will be organized so that every reports that management requested can be fulfill immediately. This system can help STIKOM Surabaya to populate academic reports and can also fulfill accreditation requirement for the government in the fastest way.